3t+3=t+3

Simple and best practice solution for 3t+3=t+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t+3=t+3 equation:


Simplifying
3t + 3 = t + 3

Reorder the terms:
3 + 3t = t + 3

Reorder the terms:
3 + 3t = 3 + t

Add '-3' to each side of the equation.
3 + -3 + 3t = 3 + -3 + t

Combine like terms: 3 + -3 = 0
0 + 3t = 3 + -3 + t
3t = 3 + -3 + t

Combine like terms: 3 + -3 = 0
3t = 0 + t
3t = t

Solving
3t = t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
3t + -1t = t + -1t

Combine like terms: 3t + -1t = 2t
2t = t + -1t

Combine like terms: t + -1t = 0
2t = 0

Divide each side by '2'.
t = 0

Simplifying
t = 0

See similar equations:

| -12/13/X/4= | | f(x)=20(1.3) | | f=-3.5+2x | | [(-2)+7-(-5)]+[-4-(-10)]= | | -9N-6+2N= | | 8xs+40=16 | | -x=-2y-4 | | 3x((17-9x)-(16x-10))=30-23x | | 5x+3=168 | | y-2.8=7.24 | | 2x+3y=229 | | 0=3r^2-8r+1 | | 8x-1x=2 | | 6y^2-13y=6 | | 3x+9=-54-6 | | 18+3(x-4)+6= | | Y-(-2)=6/1(x-2) | | 10+12=14y-1-13y | | 3.25g+1.25g=81 | | 15X+4=10X+21 | | ay=5y+16 | | 12d=11 | | 15-3(x+5)-2= | | c-13=-1 | | 4(3p+2)-5(6p-1)=2(p-8)-6(7p-4) | | 6+4(x-1)+8= | | -12+8+(-2)= | | 5(x+4)-10= | | -2x-5=-2+1 | | 16p+14q= | | https://media.education2020.com/evresources/3108-05-05/mc018-1.jpg | | 3(x-1)+7= |

Equations solver categories